Analisis Kerusakan Kepala Silinder Blok Mesin Pada Kendaraan Jenis Minibus Kapasitas 1500 CC - Sungkono; Masyhudi; Ahmad Zayadi (FTK UNSURYA, 2023)
Four-wheeled vehicles are one of the commonly used modes of transportation. The vehicle engine has a cylinder head to place the valves and cooling mantle. Damage to the cylinder head will disrupt the engine's working system for a long time. The damaged will take a long time for the repair process. The cylinder head is usually damaged at a milage of 80,000 km. The damage experienced by the cylinder head is the emergence of a rough sound in the engine, the mixing of cooling water into the combustion chamber and the temperature rises quickly, in this study a study will be conducted on the damage that occurs to the cylinder head. Based on the results of macrostructure testing, corrosion occurs due to engine cooling fluid, besides that there is a deposit that is very strong and corrosive to the cylinder head on the engine block, microstructure testing shows the presence of (black) deposits which are thought to affect the corrosion process, dendrite grains and rods in the microstructure do not change grain size. Based on the hardness test results show the hardness value of the damaged surface of 102.22 HV and the hardness value of the undamaged surface of 102 HV based on the damage to the engine block cylinder head is not caused by material deformation due to mechanical and thermal loads. The results of the chemical composition test of the cylinder head that was damaged decreased Al 1.1%, Si 0.11%, Cu 0.37, Fe 0.088% and Mg 0.081% and the decrease in the chemical composition of the constituent elements of the material was caused by the interaction of water with the surface of the cylinder head which was characterized by the formation of oxides of Al, Si, Cu, Fe, and Mg. Based on the test results, cylinder head damage is more due to lack of maintenance of the engine block.